Tathwir Wasilah al-Ta'lim bi al-Fidiu al-Rusum al-Mutaharrikah 3D 'ala Asas Tathbiq Kine Master 'ala Madah al-Mihnah li Tullab al-Saff al-Thamin bi al-Madrasah al-Thannawiyah al-Hukumiyyah Palopo - Adrian; Mardi Takwim; M Zuhri Abu Nawas (Al Ibrah: Journal of Arabic Language Education, 2024)
This Research discusses the development of a teaching aid using animated videos based on the KineMaster application for vocational subjects for eighth-grade students at the Valuvo State Secondary School. The objectives of this study are: to test the results of developing a teaching aid with 3D animated videos based on the KineMaster application for vocational subjects for eighth-grade students at the Valuvo State Secondary School; and to test the practical application of the developed teaching aid using 3D animated videos based on the KineMaster application for vocational subjects. This study employs the research and development (R&D) method using the 4-D research model, consisting of four stages: (1) Define, (2) Design, (3) Develop, and (4) Disseminate. This research was conducted on eighth-grade students at the Valuvo State Secondary School, with 30 students participating from June to July 2023, to test the practical application of the 3D animated educational video. The results of this development are: (1) the development of a teaching aid with 3D animated videos based on the KineMaster application for vocational subjects, and (2) the validity level of the developed teaching aid with 3D animated videos based on the KineMaster application in eighth grade. According to the results of validation by media experts, the validity score was 90%, categorized as very valid; the validation by subject matter experts scored 95%, also categorized as very valid. Meanwhile, to determine the practical application level of the educational videos in this study, student assessment sheets were used, resulting in a score of 91.2%, categorized as very practical.